Whole genome sequencing of CCR5 CRISPR-Cas9-edited Mauritian cynomolgus macaque blastomeres reveals large-scale deletions and off-target edits - Schmidt, Jenna Kropp; Kim, Yun Hee; Strelchenko, Nick; Gierczic, Sarah R.; Pavelec, Derek; Golos, Thaddeus G.; Slukvin, Igor I. (Frontiers in Genome Editing, 2023)
Genome editing by CRISPR-Cas9 approaches offers promise for introducing or correcting disease-associated mutations for research and clinical applications. Nonhuman primates are physiologically closer to humans than other laboratory animal models, providing ideal candidates for introducing human disease-associated mutations to develop models of human disease. The incidence of large chromosomal anomalies in CRISPR-Cas9-edited human embryos and cells warrants comprehensive genotypic investigation of editing outcomes in primate embryos. Our objective was to evaluate on- and off-target editing outcomes in CCR5 CRISPR-Cas9-targeted Mauritian cynomolgus macaque embryos. DNA isolated from individual blastomeres of two embryos, along with paternal and maternal DNA, was subjected to whole genome sequencing (WGS) analysis. Large deletions were identified in macaque blastomeres at the on-target site that were not previously detected using PCR-based methods. De novo mutations were also identified at predicted CRISPR-Cas9 off-target sites. This is the first report of WGS analysis of CRISPR-Cas9-targeted nonhuman primate embryonic cells, in which a high editing efficiency was coupled with the incidence of editing errors in cells from two embryos. These data demonstrate that comprehensive sequencing-based methods are warranted for evaluating editing outcomes in primate embryos, as well as any resultant offspring to ensure that the observed phenotype is due to the targeted edit and not due to unidentified off-target mutations.